Lessons from Live Project: A Case Study on a Landscape Project of An Institution - Othman , Jamilah (Journal of Architecture, Planning and Construction Management, 2020)
This paper evaluates the authors’ experiences in supervising a construction of a landscape project of an institution. The works involved an upgrading of the landscape and hardscape of the main entrance, while the supervision was originally devised by several lecturers. The live project provided good impacts to both students and lecturers. For instance, live project with real problems and client has strengthened students’ practical knowledge. Secondly, live project has provided experience and knowledge for better teaching/learning of built environment subjects. It was an urgent project and thus, dateline was highly important. Though the construction had completed on time, there were complaints received; e.g. issues on the quality and project cost. These unsuccessful parts of the construction were perhaps related to several reasons such as Coordination Meetings (CMs), professionalism and ethics, and Statement Needs (SNs). This paper uses evidences drawn from site supervisions and discussion with expert/colleagues in reviewing the factors that would link to the issues. Review presents several findings, which are leading towards that; lack of skilled workers, ineffective coordination and lack of responsibility and commitment and etc. The paper suggests that good Construction Practices (CPs) can be achieved through good coordination among construction teams, organised CMs, and definite SNs. The ideas can perhaps be considered for future construction with similar nature of work. Further, the insights may also contribute significant implications to several individuals and organisations, namely stakeholder, Superintendent Officer (SO), academicians, students, contract workers, project cost, quality of works, project dateline and many more.